What you need to know about phrasal verbs : (Learners publishing, 2003)
This is a open-ended series of ELT reference books on various aspects of English specially planned for intermediate learners who want to get to grips with English. Covering the most important topics of English, the series aims at helping foreign learners build a solid foundation for the learning of the language.